Approximate Quadratic-Additive Mappings in Fuzzy Normed Spaces - Ick-Soon Chang; Yang-Hi Lee (Discrete Dynamics in Nature and Society)
We examine the generalized Hyers-Ulam stability of the following functional equation: 2fx+y+z+w+f-x-y+z+w+f-x+y-z+w+f-x+y+z-w+fx-y-z+w+fx-y+z-w+fx+y-z-w-5fx-3f-x-5fy-3f-y-5fz-3f-z-5fw-3f-w=0, in the fuzzy normed spaces with the fixed point method.